2019
DOI: 10.1111/asap.12188
|View full text |Cite
|
Sign up to set email alerts
|

Class Perceptions and Attitudes Toward Immigration and Race Among Working‐Class Whites1

Abstract: As neighborhoods that were predominantly White become more racially and ethnically diverse, many Whites in those communities respond with feelings of threat and political shifts to the right. Trump's election in 2016 has often been attributed, at least in part, to such responses among members of the White working class. Building on this work, in the summer of 2017 (and thus after the election) we interviewed 77 working-class White residents of three majority-White cities from the Midwestern United States that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 25 publications
3
19
2
Order By: Relevance
“…Indeed, tens of millions of working-class White voters opposed Trump in 2016 (Tyson & Maniam, 2016), in large part because his xenophobic and exclusionary rhetoric ran counter to their more progressive social views (Smith & Hanley, 2018). Contrary to popular political narratives (e.g., Packer, 2012), the White working class is a not a monolithic political force-raising the question of why Whites who occupy a similar socioeconomic location display such a diversity of social and political views (McDermott et al, 2019).In the present work, we argue that working-class Whites' social and political attitudes are inextricably tied to their class identities-that is, their beliefs about their own location in the socioeconomic hierarchy, about adjacent classes, and about social values worth upholding (McDermott et al, 2019). We begin by leveraging nationally-representative survey data to document the number, nature, and relative prevalence of different identity types found among working-class White adults.…”
mentioning
confidence: 51%
“…Indeed, tens of millions of working-class White voters opposed Trump in 2016 (Tyson & Maniam, 2016), in large part because his xenophobic and exclusionary rhetoric ran counter to their more progressive social views (Smith & Hanley, 2018). Contrary to popular political narratives (e.g., Packer, 2012), the White working class is a not a monolithic political force-raising the question of why Whites who occupy a similar socioeconomic location display such a diversity of social and political views (McDermott et al, 2019).In the present work, we argue that working-class Whites' social and political attitudes are inextricably tied to their class identities-that is, their beliefs about their own location in the socioeconomic hierarchy, about adjacent classes, and about social values worth upholding (McDermott et al, 2019). We begin by leveraging nationally-representative survey data to document the number, nature, and relative prevalence of different identity types found among working-class White adults.…”
mentioning
confidence: 51%
“…Particularly, previous studies have shown that increased ethno-racial diversity leads to a high degree of realistic threat under conditions in which economic resources are scarce (Quillian, 1995). Thus, the extent to which either a symbolic or realistic threat leads to outgroup hostility is influenced by the socioeconomic factors of a given context (McDermott et al, 2019; Nijs et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The roots of human rights violations lay on racializing outgroup members (or non-citizens) and constructing the "Others" (McDermott et al, 2019) to dehumanize immigrants and refugees and/or asylum-seekers, a way by which to justify state-sanctioned violence that the citizens of the migration destination country are protected from (Augoustinos et al, 2018). All participants reported experiences that involved persistent human rights violations.…”
Section: Criminalization Of Immigrantsmentioning
confidence: 99%